In the Eye of the Tornado: Encounters with Clay—A Relational Materialist Orientation Toward Cultivating Curriculum - Malki, Erin; Gutierrez, Roselyn; Skuggedal, Colleen (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2022)
This paper follows three student-educators’ journey with clay. Embedded in the contextual space of the studio, the paper considers the complexities and processes involved in cultivating curriculum and thinking with the idea of art as a language. Inspired by the relational materialist approach, Erin, Roselyn, and Colleen enter into a dialogue with clay—embodying one another, entangling with each other, intra-actively doing unto one another, and reaffirming that knowing things is embedded deeply in relational connectivity with the world around us—onto-epistemology. The authors journey together with clay through spinning, twirling, tornadoes, storms, music, chaos, and destruction.